IoT-based smart waste management system: A solution for urban sustainability - Jamil Alsayaydeh, Jamil Abedalrahim; Bacarra, Rex; Wong, Adam Yoon Khang; Mohd Yaacob, Noorayisahbe; Herawan, Safarudin Gazali (International Information and Engineering Technology Association, 2025)
Environmental waste is still a debacle in our daily lives as well as for the world. Most waste management systems do not have monitoring functionalities, which results in inefficient collection routes, higher processing costs, and environmental damage. These figures only continue to grow. In modern metropolises that are home to most population growth, people are increasingly turning to outdated systems that can no longer handle the amount of waste being produced. These systems then turn out to be too costly, which becomes a major and unsolved problem in the long run. This paper presents a secure, low-cost IoT smart waste system that integrates five sensors, HC-SR04 ultrasonic (fill-level), HX711 load-cell (weight), DHT22 (temperature/-humidity), MQ-135 gas (air quality) and Ublox NEO-6M GPS, around an Arduino-ESP8266 core and Firebase cloud analytics. A 30-day field trial on 12 municipal bins achieved 85% fill-level accuracy, < 3% mean absolute error in weight, and 100% detection of hazardous temperature (≥ 40°C) or humidity (≥ 70% RH). GPS-guided routing cut truck mileage by 20 % and CO₂ emissions by 18% versus fixed schedules (p < 0.01, paired-sample t-test). These results confirm that multi-sensor IoT retrofits can reduce operational costs while improving public-health safeguards, providing a replicable blueprint for sustainable smart-city waste infrastructure.